Riziko rakoviny plic ve vztahu k expozici radonu v pracovním a životním prostředí - prospektivní epidemiologické studie - Tomášek, Ladislav; Kunz, Emil; Plaček, Václav; Müller, Tomáš; Hůlka, Jiří; Kypěnová, Hana; Horáčková, Olga; Hradecký, Jan; Gruberová, Hana (Iga MZ ČR, 2001)
The project includes a further follow-up in two epidemiological studies of lung cancer risk from radon exposure. The objective is better understanding and more precission of risk models, particularly the effect of time. The occupational exposures of uranium miners are registered since 1948. The residential cohort accounts nearly 12000 inhabitants in a high radon specific area of Middle Bohemian Pluton, where the incidence is recorded since 1960.
Závěrečná zpráva o řešení grantu Interní grantové agentury MZ ČR
Keywords: Air Pollution, Indoor; nádory plic; Radon; rizikové faktory; prospektivní studie; radioaktivní znečištění ovzduší; pneumologie a ftizeologie; Air Pollution, Radioactive; epidemiologie; Lung Neoplasms; znečištění vzduchu ve vnitřním prostředí; hodnocení rizik; Risk Assessment; radiační ochrana; Prospective Studies; radon; Risk Factors